Pengaruh Kualitas Produk terhadap Keputusan Pembelian dengan Harga sebagai Variabel Moderasi di Nawa Bistro Solo - Aulia Nanda Asy A; Putri Lindiani Agata; Aulia Miftahul Karimah; Marjam Desma Rahadhini (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of product quality on purchasing decisions with price as a moderating variable at Nawa Bistro Solo. Using a quantitative approach with causal-comparative design, data were collected through online questionnaires from 48 respondents selected by purposive sampling. The research instrument consisted of 20 question items with a Likert scale of 1-5 that had been tested for validity and reliability. Data analysis used moderation regression with classical assumption tests. The results show that product quality has a significant positive effect on purchasing decisions with a regression coefficient of 0.612 (p < 0.05). Price proved to act as a moderating variable that strengthens the relationship between product quality and purchasing decisions with an interaction coefficient of 0.284 (p < 0.05). The majority of respondents (77.1%) showed positive purchasing decisions and 66.7% gave positive assessments of product quality. These findings imply that appropriate value-based pricing strategies can optimize the impact of product quality on consumer loyalty in the culinary industry.